The Reality of Students’ Attitudes toward the Autonomy of Universities in Light of the New University System: A Field Study at King Abdulaziz University in Jeddah Governorate - Al-Harbi, Ahmed Ghazi; Hassan, Taibah Abdulqadir (The Arab Journal of Administration, 2025)
The study aimed to find out the reality of students’ attitudes towards the autonomy of universities in light of the new university system. The study used a descriptive analytical approach to prepare a questionnaire on the dimensions related to the autonomy of universities (Administrative, financial, academic), and it was applied to a sample of (162) students from King Abdulaziz University in Jeddah Governorate for the academic year 1445 AH. The study found that the students’ attitudes toward administrative independence at the university reached a mean of (3.3560), and their attitudes toward the financial independence of the university under study reached (3.6726), while the students’ attitudes regarding the academic independence of the university amounted to (3.6726). Accordingly, the study recommended creating an interactive communication channel that enables students’ voices to be heard about their visions for developing the university according to the new university system, promoting the interest of students through the three elements of independence (administrative, financial, and academic), the study also recommended working to give universities the full opportunity to absorb the new university system.